2007 IEEE Radiation Effects Data Workshop 2007
DOI: 10.1109/redw.2007.4342557
|View full text |Cite
|
Sign up to set email alerts
|

Compendium of Current Single Event Effects Results for Candidate Spacecraft Electronics for NASA

Abstract: Abstract-Sensitivity of a variety of candidate spacecraft electronics to proton and heavy ion induced single event effects is presented. Devices tested include digital, linear, and hybrid devices.Index Terms-Single Event Effects, spacecraft electronics, digital, linear bipolar, and hybrid devices.In order to meet the demands of reduced cost. higher performance and more rapid delivery schedules imposed by the space flight community, commercial and emerging technology devices have assumed a prominent role in mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…According to the experimental data published in Refs. [13,14], we found that although the new technology is used in this device, effectively eliminating SEL, it is still very susceptible to SEU, and when compared to a 16M SRAM, which have a similar feature size and structure, SEU was found to occur even when the LET value is as low as 1.73 MeV-cm 2 /mg [13]. From Ref.…”
Section: Experimental Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the experimental data published in Refs. [13,14], we found that although the new technology is used in this device, effectively eliminating SEL, it is still very susceptible to SEU, and when compared to a 16M SRAM, which have a similar feature size and structure, SEU was found to occur even when the LET value is as low as 1.73 MeV-cm 2 /mg [13]. From Ref.…”
Section: Experimental Descriptionmentioning
confidence: 99%
“…From Ref. [13], we found that for such large-capacity and small-sized devices, it is usually difficult to measure its saturation cross section, as multiple-bit upset normally occurs. The ion species chosen for the current work and their characteristics are listed in Table 1.…”
Section: Experimental Descriptionmentioning
confidence: 99%
“…The AD654 is a voltage-to-frequency converter from Analog Devices that was previously total dose tested and found to exceed the full scale error at 18 krad(Si) and the input bias current at 8 krad(Si) [1]. The part was tested at a dose rate of 20 mrad(Si)/s (because of time constraints) in the configuration that will be used for flight, which was different from that specified in the data sheet.…”
Section: ) Analog Devices Ad654 Voltage-to-frequency Convertermentioning
confidence: 99%
“…With the development of aircraft avionics, the scale of electronic circuits in aircraft presents geometric growth, and the electronic computing components in aircraft system equipment are highly integrated and the operation logic is getting more and more complex. All these leads to the occurrence of single events more and more frequently [3][4][5][6][7]. The SEE phenomenon is particularly evident in the high-latitude and high-altitude civil aviation routes.…”
Section: Introductionmentioning
confidence: 99%